WATER POTABILITY OF CACIMBAS: CASE STUDY IN A DISTRICT OF THE CITY OF BARRO, CEARÁ - Souza, S. R.; Sousa, E. O. (Revista Brasileira de Engenharia de Biossistemas, 2020)
Several factors can affect the water quality of cacimbas, which makes it necessary to monitor it for human consumption. In this sense, the present work sought to analyze a physical-chemical and microbiological quality of water from cacimbas in the rural area of the district of Iara, city of Barro, Ceará. The waters were collected directly from the tanks in sterile containers, then they were stored in thermal boxes with ice for conservation and transported for analysis in the laboratory. Physical-agglomerated analyzes were performed to determine turbidity, electrical conductivity, total hardness, chlorides, ammoniacal nitrogen, nitrate, nitrite, pH, aluminum, total iron, total dissolved solids and manganese, and microbiological analyzes to determine total coliforms and Escherichia coli. The results hindered that most of the proven water of the cacimbas quality independent in relation to the physico-chemical parameters, but some changes in relation to the durability, and the nitrate and iron terrors. All samples showed microbiological contamination by total coliforms and only one had no contamination by E. coli. The data reinforce the question of the susceptibility of cacimbas to various contamination factors and the need for greater measures to revert the population that cause the contamination of cacimbas.